Destination Resources in Ecotourism on Satisfaction and Revisit Intention: Digital Inclusion on Social Media Marketing in Sarawak National Parks and Nature Reserves - Sandra Ying Ying, Khoo; Lo, May Chiun; Abang Azlan, Mohamad (Universiti Malaysia Sarawak, 2025)
This study addresses the need for innovative marketing strategies in Sarawak’s ecotourism sector, focusing on how destination resources such as tourism infrastructure, service quality, natural resources and cultural heritage impact tourists’ satisfaction and revisit intention. The specific objectives are to examine the relationships between these destination resources and tourists’ satisfaction and revisit intention, and to assess the moderating role of social media marketing in these relationships. The study employs SPSS version 27.0.1.0 and Warp PLS 8.0 for descriptive statistics and the examination of measurement and structural models. The findings indicate that tourism infrastructure, service quality, natural resources, and cultural heritage positively influence tourists’ satisfaction and revisit intention. However, social media marketing significantly moderates only the relationship between natural resources and tourists’ satisfaction. These results suggest that while traditional destination resources remain crucial, integrating social media marketing can enhance the impact of natural resources on tourists’ satisfaction, offering practical insights for ecotourism marketers and policymakers.